Return to Play in Football An Evidence-based Approach (Springer Berlin Heidelberg, 2018)
In this book, leading experts employ an evidence-based approach to provide clear practical guidance on the important question of when and how to facilitate return to play after some of the most common injuries encountered in football. Detailed attention is paid to biomechanics, the female athlete, risk factors, injury prevention, current strategies and criteria for safe return to play, and future developments. Specific topics discussed in depth include concussion, anterior cruciate ligament and other knee injuries, back pathology, rotator cuff tears, shoulder instability, hip arthroscopy, and foot and ankle injuries. The chapter authors include renowned clinicians and scientists from across the world who work in the field of orthopaedics and sports medicine. Furthermore, experiences from team physicians involved in the Olympics, National Football League (NFL), Union of European Football Associations (UEFA), and Fédération Internationale de Football Association (FIFA) are shared with the reader. All who are involved in the care of injured footballers will find this book, published in cooperation with ESSKA, to be an invaluable, comprehensive, and up-to-date reference that casts light on a range of controversial issues.